Agency and Communion Predict Speaking Up in Acute Care Teams. (June 2014) - Weiss, Mona; Kolbe, Michaela; Grote, Gudela; Dambach, Micha; Marty, Adrian; Spahn, Donat R.; Grande, Bastian
Speaking up with suggestions, problems, or doubts is important—especially in health care action teams where each team member's input can be crucial for the treatment of a patient. Implementing a high-fidelity simulation study, we investigated individual predictors of speaking up in acute care teams (ACTs). Participants were 27 physicians and 27 nurses from a hospital who completed measures on self-perceived agency (i.e., assertiveness, persistence, independence) and communion (i.e., helpfulness, friendliness, sociability). In two-person teams, they managed simulated critical events that required speaking up. In line with our hypotheses, we found that agency positively and communion negatively predicted actual speaking up behavior. We discuss the differential effects of agency and communion on speaking up and thereby highlight theoretical and practical implications.